1999
DOI: 10.1159/000025910
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Factors and Tubulointerstitial Injury

Abstract: Morphological changes of the tubulointerstitial architecture are a major determinant in the progression of chronic renal disease. The evolution of the tubulointerstitial lesion includes early tubular hypertrophy, recruitment of inflammatory cells into the tubulointerstitial space, and proliferation of interstitial fibroblasts resulting in the irreversible changes of tubular atrophy and tubulointerstitial fibrosis. Many of these diverse effects are mediated by autocrine or paracrine release of growth factors, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…Diabetic nephropathy is characterized by excessive deposition of ECM in the kidney, leading to glomerular mesangial expansion and tubulointerstitial fibrosis. Recent studies have demonstrated that early renal hypertrophy is detrimental to the kidney in the long term and is a precursor of development of renal fibrosis [19,20] . Although the exact mechanisms of renal hypertrophy are still unclear, several growth factors, cytokines, chemokines, and vasoactive agents have been implicated in the development of renal hypertrophy, which include TGF-β, insulin like growth factor-1 (IGF-1), and platelet derived growth factor (PDGF) [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy is characterized by excessive deposition of ECM in the kidney, leading to glomerular mesangial expansion and tubulointerstitial fibrosis. Recent studies have demonstrated that early renal hypertrophy is detrimental to the kidney in the long term and is a precursor of development of renal fibrosis [19,20] . Although the exact mechanisms of renal hypertrophy are still unclear, several growth factors, cytokines, chemokines, and vasoactive agents have been implicated in the development of renal hypertrophy, which include TGF-β, insulin like growth factor-1 (IGF-1), and platelet derived growth factor (PDGF) [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…The pleotropic actions of angiotensin II include the stimulation of matrix protein formation and deposition leading to fibrosis in a variety of tissues including heart [1,2] , vascular tissue [3][4][5][6] , kidney [7][8][9][10][11][12][13] , liver [14,15] , lung [16] and retina [17] . The effect of angiotensin II is mediated by upregulation of connective tissue growth factor (CTGF) [15,[18][19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Although all the structural components of the nephron are involved in such responses, enlargement of proximal tubular epithelial cells principally accounts, in quantitative terms, for the predominant component of compensatory renal hypertrophy [1]. Recent studies have demonstrated that tubular hypertrophy is detrimental to the kidney in the long term and serves as a precursor of development of tubulointerstitial fibrosis [2, 3]. It is therefore important to clarify the exact mechanisms of tubular epithelial cell hypertrophy, which may provide a new strategy to prevent renal fibrosis early.…”
Section: Introductionmentioning
confidence: 99%